PENGEMBANGAN KAPASITAS BADAN PENELITIAN DAN PENGEMBANGAN DAERAH PROVINSI NUSA TENGGARA TIMUR - Wehelmina Lodia Kause (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
Research and Local Development Institute (Balitbangda) in East Nusa Tenggara Province as a scientic specific based organization need to adopt adaptive learning through capacity building . This study discusses and analyze capacity building organization structure and humman resources. The result showed the work is hierarchically by devision of labor according to job of struktural and functional positions. Devision of labor by structural job not yet based on specialization professionall but a researcher base on professionalism. Authority is at the High Leader level and task and responsibility delegates are hierarchically at the lower levels. In general human resources Balitbangda NTT province educated undergraduate but still minimal methodology and scientific substance.Keywords: capacity building, learning organization, human resources